Filsafat Ilmu dan Studi Islam: Filsafat Ilmu-Ilmu Keislaman - Nurima, Andi; Ahmad, La Ode Ismail (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The main problem that has emerged in the modern era is that many Islamic sciences have developed only as practical disciplines, but their ontological foundations (the nature of the object of study), epistemological (how to acquire knowledge), and axiological (ethical goals and uses) are not discussed in depth. The purpose of this study is to discuss the philosophy of science starting from its definition and relevance to Islamic studies. In addition, the epistemology of bayani, burhani, and irfani in Islamic sciences, as well as the character and purpose of Islamic sciences, will be discussed. The methodology used in this study is qualitative using descriptive analysis with library research in collecting data. The results of this study are that the philosophy of science functions to uncover the ontological, epistemological, and axiological foundations of science, so it is very relevant to Islamic studies because it helps understand the sources of knowledge (revelation–reason–experience), methods of interpretation, and the scientific foundations of Islamic disciplines. The epistemological frameworks of bayani, burhani, and irfani demonstrate that Islamic sciences develop through three paths of knowledge: text, reason, and spiritual experience, which complement each other in building the edifice of Islamic knowledge.